MENGEMBANGKAN BILLIARD MINI UNTUK MENINGKATKAN KONSENTRASI PADA ANAK AUTIS - Karunia Yulinda Khairiyah; Rahmat Sanusi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article refers to developmental research related to the Borg & Gall research concept with seven modified development steps. The purpose of the study in this article was to produce a product namely mini billiards to increase the concentration of children with autism. To ensure whether the product was suitable for use or not, it also involved an expert assessment consisting of Learning Media Experts, Learning Experts of Special Needs Children, and Recreational Sports Small Game Experts. The product trial was divided into two stages, a smallscale trial involving 13 students with autism and a large-scale trial involving 20 students with autism. Data collection techniques used observation, interviews, and questionnaires. The data analysis technique used a qualitative descriptive technique. Based on the results of expert assessments and trials, the product was a good category. Clearly, the product was suitable for use to increase concentration in children with autism.